Mapping policies for surface water protection zones on forest land in the Nordic-Baltic region: Large differences in prescriptiveness and zone width - Ring, Eva; Johansson, Johanna; Sandström, Camilla; Bjarnadottir, Brynhildur; Finér, Leena; Libiete, Zane; Lode, Elve; Stupak, Inge; Saetersdal, Magne (Springer, 2017)
The forest landscape across the Nordic and Baltic regions hosts numerous lakes and watercourses, which must be included in forest management. In this study, national policy designs regarding protection zones for surface waters on forest land were reviewed and compared for the Nordic countries, Estonia and Latvia. The focus was how each country regulates protection zones, whether they are voluntary or mandatory, and the rationale behind adopting a low or high degree of prescriptiveness. Iceland and Denmark had a low degree of policy prescriptiveness, whereas Norway, Estonia and Latvia had a high degree of prescriptiveness. Sweden and Finland relied to a large extent on voluntary commitments. The prescribed zone widths within the region ranged from 1 m to 5 km. The results indicated that land-use distribution, forest ownership structure and historical and political legacies have influenced the varying degrees of prescriptiveness in the region.
Keywords: buffer; certification; Suomi; Pohjoismaat; Latvia; Viro; metsämaa; vesiensuojelu; lainsäädäntö; forest land; water protection; legislation